(untitled) (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
Online transportation applications have become an increasingly important mobility alternative for university students, primarily due to cost efficiency and service convenience. This study analyzes the economic impact of using the Maxim application among students of the Faculty of Economics and Business, Widya Mandira Catholic University Kupang, and examines the influence of fares, accessibility, travel time, service quality, and promotional offers on the level of Maxim usage. A quantitative approach was employed with 100 purposively selected respondents, and the data were analyzed using multiple linear regression. The findings indicate that Maxim use provides a transportation cost efficiency of approximately 20–30% compared to prior transportation expenses. Simultaneously, all independent variables significantly affect Maxim usage. However, partial tests show that only fares and accessibility have significant effects, while travel time, service quality, and promotions do not. These results reinforce consumer behavior and rational choice theories, suggesting that students prefer transportation services that minimize costs and offer easy access to ordering. The study highlights the economic relevance of Maxim as a practical transportation alternative for students and offers implications for application developers, university administrators, and local policymakers.